Dynamical behavior of cancer cell densities in two dimensional domain by the representation theory of solitons - Iqbal, Muhammad Sajid; Ahmed, Nauman; Naeem, Rishi; Akgul, Ali; Razzaque, Abdul; İnç, Mustafa; Khurshid, Hina (Elsevier, 2023)
This article analyzes the mathematical model which is described by the nonlinear partial differential equation governing the density of cancer cells at any position (x, y) in the open bounded subset of the plane at any time t. This is a two-dimensional model that describes the dynamics of cancer cells under radiotherapy and its comparison with the one in the absence of radiation effects. The 06-model expansion method has been used to find the exact solutions of the underlying problem. The simulation of obtained results have also been argued.(c) 2023 Elsevier B.V. All rights reserved.
Keywords: Density of cancer cells; Population dynamics; Exact solutions; ø (6) method